Financial Access and Financial Literacy on the Performance of MSMEs in Solok City - Roza, Seflidiana; Sriyanti, Esi; Zahran, Althaf Naufal (Journal of International Accounting, Taxation and Information Systems, 2025)
This research aims to examine the influence of financial inclusion and financial literacy on the performance of Micro, Small, and Medium Enterprises (MSMEs), specifically 3 kg LPG gas depots located in Bukit Sundi and Kubung Districts, Solok Regency. MSMEs in this area still face various obstacles, particularly limited access to formal financial services and low understanding of business operators regarding financial management. The study employs a quantitative method utilizing multiple linear regression to analyze primary data obtained from surveys completed by 40 gas depot owners. Findings indicate that financial literacy positively impacts MSME performance, although financial inclusion does not have a significant partial effect. Nevertheless, when considered together, both variables significantly influence business performance. This finding confirms the importance of improving financial literacy for MSME operators rather than merely expanding access to financial services. This research recommends that future studies consider additional variables such as work incentives, human resource quality, and productivity to obtain a more comprehensive understanding of the factors that influence MSME performance.